A Lifespan Approach to Balance in Static and Dynamic Conditions: The Effect of Age on Balance Abilities - Marchesi, Giorgia; De Luca, Alice; Squeri, Valentina; De Michieli, Lorenzo; Vallone, Francesco; Pilotto, Alberto; Leo, Alessandra; Casadio, Maura; Canessa, Andrea (Frontiers in Neurology, 2022)
Postural control is a complex sensorimotor skill fundamental in our daily life. The abilities to maintain and recover balance degrade with age. However, the time-decay of balance performance with age is not well understood. In this study, we aim at quantifying the age-dependent changes in standing balance under static and dynamic conditions. We tested 272 healthy subjects with ages ranging from 20 to 90. Subjects maintained the upright posture while standing on the robotic platform hunova®. In the evaluation of static balance, subjects stood on the fixed platform both with eyes open and closed. Then, in dynamic condition, subjects stood with eyes open on the moving foot-platform that provided three different perturbations: (i) inclination proportional to center of pressure displacements, (ii) pre-defined predictable motion, and (iii) un-predictable and un-expected tilt. During all these tests, hunova® measured the inclination of the platform and the displacement of the center of pressure, while the trunk movements were recorded with an accelerometer placed on the sternum. To quantify balance performance, we computed spatio-temporal parameters typically used in clinical environments from the acceleration measures: mean velocity, variability of trunk motion, and trunk sway area. All subjects successfully completed all the proposed exercises. Their motor performance in the dynamic balance tasks quadratically changed with age. Also, we found that the reliance on the visual feedback is not age-dependent in static conditions. All subjects well-tolerated the proposed protocol, independently of their age, without experiencing fatigue, as we chose the timing of the evaluations based on clinical needs and routines. Thus, this study is a starting point for the definition of robot-based assessment protocols aiming at detecting the age-related onset of standing balance deficits and allowing the planning of tailored rehabilitation protocols to prevent falls in old adults.